Dialektika Modernis dan Tradisionalis ‎ Pemikiran Hukum Islam Di Indonesia ‎(Pemikiran Hukum Islam KH. Ahmad Sanusi 1888-1950)‎ - Yayan Suryana (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
This article presents an analysis on the construction of thought of K.H Ahmad Sanusi, a Islamic cleric originated from Sukabumi, East Java. He was highly involved in the intellectual contestation between traditionalist Muslims and their modernist counterpart. In some of his opinions about Islamic law, Sanusi positioned himself in the middle of the two opposing camps. In some occasions he leaned towards traditionalists as occasionally he with modernists Muslims launched critiques towards the traditionalists.Such ambiguous position aroused question as to the true stance of Sanusi within the debates and movements within modernist-traditionalist Muslims in Indonesia. The answer to that puzzle is that Sanusi can be considered as traditionalist-progressive or modernist-culturalist. He embraced Islamic school of law yet proposed renewals in its intellectual framework as well as its actual social programs. He maintained religious practices of the traditionalists, such as tradition of embracing school of law to which the modernists launched their criticisms. At the same moment, he did not limit himself to Shafi’iy school of law, opened his mid to other schools, acknowledged the spirit of ijtihad (legal interpretation), studied and wrote a lot on the Qur’anic exegesis, opened schools with were firstly introduced by the Dutch, and remained accommodative to local tradition and culture.